Genome-Wide Transcription Start Site Mapping and Promoter Assignments to a Sigma Factor in the Human Enteropathogen Clostridioides difficile - Soutourina, Olga; Dubois, Thomas; Monot, Marc; Shelyakin, Pavel V.; Saujet, Laure; Boudry, Pierre; Gelfand, Mikhail S.; Dupuy, Bruno; Martin-Verstraete, Isabelle (Frontiers in Microbiology, 2020)
The emergent human enteropathogen Clostridioides difficile is the main cause of diarrhea associated with antibiotherapy. Regulatory pathways underlying the adaptive responses remain understudied and the global view of C. difficile promoter structure is still missing. In the genome of C. difficile 630, 22 genes encoding sigma factors are present suggesting a complex pattern of transcription in this bacterium. We present here the first transcriptional map of the C. difficile genome resulting from the identification of transcriptional start sites (TSS), promoter motifs and operon structures. By differential RNA-seq approach, we mapped more than 1000 TSS upstream of genes. In addition to these primary TSS this analysis revealed complex structure of transcriptional units such as alternative and internal promoters, potential RNA processing events and 5' untranslated regions. By following an in silico iterative strategy that used as an input previously published consensus sequences and transcriptomic analysis, we identified candidate promoters upstream of most of genes and non-coding RNAs. This strategy also led to refine consensus sequences for the major sigma factors of C. difficile. Among the still uncharacterized regulon of the major sigma factors of C. difficile, we defined the SigL regulon by combining transcriptome and in silico analyses. We showed that SigL regulon is largely involved in amino-acid degradation, a metabolism crucial for C. difficile gut colonization. Finally, we combined our TSS mapping, in silico identification of terminators and RNA-seq data to improve gene annotation and to suggest operon organization in C. difficile. These data will considerably improve our knowledge of global regulatory circuits controlling gene expression in C. difficile and will serve as a useful rich resource for scientific community both for the detailed analysis of specific genes or systems biology studies.